WELLBEING, SCHIZOPHRENIA AND EXPERIENCE MACHINES - Birks, David Rhys (Bioethics, 2013)
In the USA and England and Wales, involuntary treatment for mental illness is subject to the constraint that it must be necessary for the health or safety of the patient, if he poses no danger to others. I will argue against this necessary condition of administering treatment and propose that the category of individuals eligible for involuntary treatment should be extended. I begin by focusing on the common disorder of schizophrenia and proceed to demonstrate that it can be a considerable harm to a person's life without causing the person to be a danger to himself. I illuminate this claim by constructing a thought experiment concerning a person who slips on a banana peel and falls into a malfunctioning version of Robert Nozick's experience machine. I propose that the reasons why we should remove the person from the machine are the same reasons why we should administer involuntary treatment to individuals with schizophrenia. I rebut three objections to the analogy and conclude that if we believe that we have a duty to provide treatment for reasons relating to a person's wellbeing, it follows that we should reject the health or safety requirement and instead broaden the category of individuals who are eligible for involuntary treatment.